Genetic Diversity of Yellow and Red Berries Arabica Coffee Populations Grown in a Mix Populations in Garut, West Java, Indonesia, Based on SSR Markers - Cahyono, Andy Agus; Ardie, Sintho Wahyuning; Rubiyo, Rubiyo; Sudarsono, Sudarsono (Journal of Tropical Crop Science, 2024)
Farmers in Garut, West Java, grow mixed varieties of Arabica coffee (Coffea arabica L.). Subsequently, they use harvested beans as seeds. Intercrossing among varieties may result in hybrid progenies and harvesting hybrid progenies as seed results in genetic variations. This research aims to evaluate the genetic diversity of Arabica coffee grown in a mixed population. Ninety-one Arabica coffees comprised 37 Arabica cv. “Ahernt GRT KN” (yellow-), 45 “Sigararutang” (red-), and nine “S795” (red berries) were sampled. Twenty SSR primer pairs were validated using 15 samples representing three varieties; six were polymorphic and used to genotype 91 Arabica accessions. Genetic data were analyzed using PowerMaker 3.25 and Darwin version 6 software. The results showed that the six SSR loci generated from 2 – 3 alleles, with an average of 2.17 alleles per locus. Genetic analysis of Arabica coffee from Garut, West Java, generated SSR markers with an average PIC of 0,33 across loci and varieties. The PIC within Arabica coffee cv. “Ahernt GRT KN” and “Sigararutang” were low, and within “S795” was moderate. Those PICs indicate the presence of more genetic diversity within “S795” than the other two cultivars. The Ho across Arabica coffee cv. “Sigararutang” and “S795” were lower than the He values, confirming their self-pollination nature. However, the Ho values of Arabica coffee cv. “Ahernt GRT KN” was larger than the others, indicating the presence of residual heterozygosity and a low percentage of recent outcrossing. The low Ho values of “Sigararutang” suggest that Arabica coffee is homozygous. Arabica coffee cv. “S795” also showed a low Ho value, but its moderate He value indicates the presence of more genetic diversity than the othercultivars.